ANALYSIS AND DESIGN OF WHEAT DISTRIBUTION SYSTEM IN PORT AREA BANTEN - Ekawati, Ratna; Anggraeni, Shanti Kirana; Wahyuni, Nuraida; Febianti, Evi (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
The globalization of free trade has caused imported food to become an alternative consumption because of the ease of consumption, such as fast food. Wheat demand fluctuates due to increased demand for making wheat flour by factories around the port area. Indonesia, which does not have productive wheat plantations, imports to meet national needs. The stakeholders in the wheat supply and distribution chain are the ports where transport ships from abroad dock. In the Banten region, the Cigading port is a loading and unloading port for wheat, corn and other agricultural grain commodities. Partner companies manage the delivery of farm commodities from loading and unloading with the help of transportation modes such as trucks, trains and conveyors for factories around the port. Imported wheat from country A is docked at the port, the loading and unloading process and delivered to several warehouses between the dry warehouse at the port and the surrounding factory warehouse. The method of transporting wheat commodities is by trucks and trains when shipping. The research aimed to optimize the number of grain truck transportation modes so that minimum distribution costs per truck can be obtained using the integer linear programming method. Minimize total distribution costs of 435.5, with truck routes sending wheat to dry warehouses inside the port and factory warehouses outside the port 12 times back and forth. That is caused by weather, long loading and unloading times, limited transportation capacity, and irregular truck queues. Keywords: distribution costs, imported, truck ration, wheat, wheat flour